Virtualized Gamified Pharmacy Simulation during COVID-19 - Denise L. Hope; Gary D. Grant; Gary D. Rogers; Michelle A. King (Pharmacy, 2022)
Extended and immersive gamified pharmacy simulation has been demonstrated to provide transformative learning in pharmacy education, preparing graduates for real-world practice. An international consortium of universities has implemented local adaptations of the Pharmacy Game into their curricula. From early 2020, pharmacy academics modified the delivery of gamified simulation in response to the COVID-19 pandemic, while still aiming to deliver the important learning outcomes of enhanced communication, collaboration, confidence and competence. Australian universities went into full lockdown from March 2020, and the critical gamified simulation at Griffith University was delivered entirely virtually in 2020. An array of synchronous and asynchronous approaches and software platforms was employed, including Microsoft Teams, Forms and Stream plus the online interview platform Big Interview. These allowed for the simulation activities, including dispensing, counselling and clinical cases, to be conducted by students online. In 2021, Griffith University conducted hybrid delivery of its Pharmacy Game, balancing student participation both in person and online. Microsoft Power Apps was added to the hosting platform to enhance the simulation interface, and Power Virtual Agent artificial intelligence chatbots, with natural language processing, were used to enable asynchronous clinical interaction. The combination of learning technologies provided the means to deliver successful gamified simulation in the virtual and hybrid environments while still achieving outstanding learning outcomes from the capstone activity. This paper details the technologies used to virtualize the Australian Pharmacy Game and the analytics available to educators to assess student participation, engagement and performance.